CVD diamond probes for nanotechnology - Niedermann, Philippe; Hänni, W.; Morel, D.; Perret, A.; Skinner, N.; Indermühle, P.-F.; de Rooij, Nicolaas F.; Buffat, P.-A. (My University, 1998)
Diamond tips are attractive tools for nanoscience because of their hardness and, when doped chemical vapor deposited (CVD) diamond is used, their electrical conductivity. In this article, devices based on CVD diamond coated silicon tips and molded diamond pyramids are described. A new type of tip, with a controlled selectively deposited diamond coating, on its upper part only, is presented, which will be useful for integration with actuators, sensors, etc. Pyramidal diamond tips with cantilevers have been micromachined and characterized, with apex radii in the range 10 to 40 nm. Structuring the diamond layer by reactive ion etching resulted in a very well defined shape of the cantilever. From resonance frequency measurements, Young's modulus of the diamond cantilevers was found to be in agreement with reported values. Preliminary tests have shown the pyramidal tips to be suitable for atomic force microscopy.